Pengaruh Sistem Informasi Akuntansi Penjualan dan Penerimaan Kas Terhadap Pengendalian Internal Pada PT Alfa Scorpii Cabang Bilal - Grace Mariana Makdalena; Galih Supraja; Tia Novira Sucipto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of the Sales Accounting Information System and the Cash Receipt Accounting Information System on Internal Control at PT Alfa Scorpii, Bilal Branch. The population in this study was 38 employees, with a sampling technique using the census method, so that the entire population was used as a research sample. The approach used in this study is quantitative associative, with data analysis techniques using Multiple Linear Regression Analysis. Data processing was carried out using SPSS version 23. The results of the study indicate that the Sales Accounting Information System has a partial positive effect on Internal Control. In addition, the Cash Receipt Accounting Information System also has a partial positive effect on Internal Control. Simultaneously, the Sales Accounting Information System and the Cash Receipt Accounting Information System have a positive and significant effect on Internal Control.